1992
DOI: 10.1143/jjap.31.3045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mn Ions on the Piezoelectric Property of (Pb, La)(Zr, Ti)O3

Abstract: The effects of sintering temperature and manganese concentration on microstructure and electromechanical property were studied in [Pb0.9La0.1][Zr0.5Ti0.5]O3 piezoelectric ceramics with the substitution of the B-site by manganese by means of scanning electron microscope (SEM) and electron spin resonance (ESR). Grain growth is enhanced by increasing temperature but suppressed by manganese substitution. There was no relationship between Qm (inverse of mechanical vibration loss) and the grain size. Some part of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…It is reported that the valence of manganese ions is partially reduced to Mn 2þ during sintering, and the oxygen vacancy is produced by the compensation effect. 11,12) However, the valence state and the distribution of manganese ions are not determined from the X-ray photoelectron spectra or the energy dispersive X-ray analysis due to the energy limitation of the equipment and to the characteristic excitation peaks of manganese being masked by those of iron. It is considered that these complex defects are dispersed in the grains, not condensed in the grain boundaries, since a complete solid solution is formed in the Mn-doped PFN ceramics when the doping concentration is below 0.75 mol%.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the valence of manganese ions is partially reduced to Mn 2þ during sintering, and the oxygen vacancy is produced by the compensation effect. 11,12) However, the valence state and the distribution of manganese ions are not determined from the X-ray photoelectron spectra or the energy dispersive X-ray analysis due to the energy limitation of the equipment and to the characteristic excitation peaks of manganese being masked by those of iron. It is considered that these complex defects are dispersed in the grains, not condensed in the grain boundaries, since a complete solid solution is formed in the Mn-doped PFN ceramics when the doping concentration is below 0.75 mol%.…”
Section: Resultsmentioning
confidence: 99%
“…2(g)). Yoo et al [12] and Izaki et al [11] had also found a similar phenomenon and it was found to be attributed to the impurities that concentrated at the grain boundaries which were obstacles for the boundary moving at high temperature and the concentration of the solute segregation was one of the majors factors which suppressed the final grain size.…”
Section: Effects Of Additives On Microstructural and Structurementioning
confidence: 72%
“…14.2 Leakage current density (J) as a function of electric field (E) applied along the a axis at 25 C for Bi 2 WO 6 -based crystals a higher s by about half orders of magnitude than BW. It has been reported that Mn occupies the B site in perovskite oxides [41,119]. The higher oxide-ion conductivity for Mn-BW is direct evidence that Mn substitution at the W 6+ site leads to an increase in V O , which is a result of the charge compensation as described below.…”
Section: Defect Control and Propertiesmentioning
confidence: 80%